Multi-metal co-regulated layered oxide sodium ion battery positive electrode material as well as preparation method and application thereof
Through the layered sodium oxide sodium ion battery positive electrode material controlled by polymetallic metal, the problems of complex phase transformation and structural collapse of the sodium ion battery positive electrode material during the cycle process are solved, excellent cycle stability and electrochemical performance are achieved, and the commercial development of sodium ion battery is promoted.
Patent Information
- Application Number
- CN202510368662.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-06-13
AI Technical Summary
The complex phase transition process of existing sodium ion battery cathode materials during the cycle process limits its commercialization process, and the sodium ion migration is difficult, which easily leads to structural collapse.
The positive electrode material of layered sodium oxide ion battery co-regulated by polymetals is Na0.96Ca0.02Ni0.27Fe0.2Mn0.35Al0.02Cu0.1Ti0.05O2 was prepared by solid phase method to improve its cycle stability and electrochemical properties.
The excellent cycle stability and electrochemical performance of the positive electrode material of sodium ion battery are achieved, which reduces costs and promotes the commercial development of sodium ion battery.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium-ion batteries, and particularly relates to a layered oxide sodium-ion battery cathode material co-regulated by multiple metals with excellent electrochemical performance, a preparation method thereof, and an application thereof. Background Art
[0002] As an efficient energy storage tool, sodium-ion batteries can effectively store renewable energy and achieve stable power supply. Due to the scarcity of resources and high cost of lithium-ion batteries, it is difficult to meet the requirements of large-scale energy storage systems. Sodium resources are abundant, widely distributed, and inexpensive on the earth, providing a resource advantage for the development of sodium-ion batteries. However, the relatively large sodium ion radius makes it more difficult to migrate during the electrochemical cycling process compared to lithium ions, and it is prone to cause structural collapse. Therefore, it is necessary to find more suitable cathode electrode materials to reduce this adverse effect.
[0003] Among them, due to its high working voltage and electrochemical capacity, etc., transition metal layered oxide materials have been widely studied as sodium-ion battery cathode materials. However, the complex phase transition process of this material during cycling limits its commercialization process.
[0004] Based on this, it is urgent to design more suitable modification strategies to obtain high-performance and long-stability sodium-ion battery cathode materials. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a layered oxide sodium-ion battery cathode material co-regulated by multiple metals and a preparation method thereof. The cathode material provided by the present invention has excellent cycle stability, and the entire synthesis process is simple and has a high yield.
[0006] The present invention adopts the following technical solutions to achieve the purpose: The present invention provides a layered oxide sodium-ion battery cathode material co-regulated by multiple metals, and the chemical formula of the sodium-ion battery cathode material is Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 .
[0007] The present invention also provides a preparation method of a layered oxide sodium-ion battery cathode material co-regulated by multiple metals, and the solid-phase method is used to synthesize the sodium-ion battery cathode material.
[0008] As an aspect of the present invention, the steps for preparing a multi-metal co-regulated layered oxide cathode material for a sodium-ion battery by a solid-phase method are as follows: Put the sodium source compound, nickel source compound, copper source compound, calcium source compound, iron source compound, manganese source compound, aluminum source compound, and titanium source compound in a mortar according to the molar ratio, and grind until fully mixed to obtain a precursor powder sample; Perform calcination treatment on the precursor powder sample to finally obtain a multi-metal co-regulated layered oxide cathode material for a sodium-ion battery, Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 。
[0009] As an aspect of the present invention, the sodium source compound is one or more of sodium oxalate, sodium nitrate, sodium chloride, sodium acetate, and sodium citrate; the nickel source compound is one or more of nickel oxalate, nickel nitrate, nickel chloride, nickel acetate, and nickel sulfate.
[0010] As an aspect of the present invention, the copper source compound is one or more of copper oxalate, copper nitrate, copper chloride, copper acetate, and copper sulfate; the calcium source compound is one or more of calcium oxide, calcium bicarbonate, calcium chloride, calcium bromide, and calcium iodide.
[0011] As an aspect of the present invention, the iron source compound is iron oxalate, iron nitrate, iron chloride, iron acetate, and iron sulfate; the manganese source compound is one or more of manganese oxalate, manganese nitrate, manganese chloride, manganese acetate, and manganese sulfate.
[0012] As an aspect of the present invention, the aluminum source compound is one or more of aluminum oxide, aluminum hydroxide, aluminum nitrate, aluminum phosphate, and aluminum sulfate; the titanium source compound is one or more of titanium dioxide, titanium tetrachloride, sodium titanate, and titanium phosphate; As an aspect of the present invention, the calcination is carried out in an air atmosphere, the calcination temperature is raised to 950 °C, the heating rate is 2 °C / min, the holding time is 15 h, and the final sample is obtained after cooling to room temperature.
[0013] A positive electrode sheet for a sodium-ion battery is prepared from a positive electrode material, a conductive additive, a binder, and a solvent, and the positive electrode material is selected from the multi-metal co-regulated layered oxide cathode material for a sodium-ion battery described in claim 1.
[0014] A sodium-ion battery is composed of a positive electrode sheet, a separator, an organic electrolyte, and a negative electrode sodium metal, and the positive electrode sheet is the positive electrode sheet for a sodium-ion battery described in claim 9.
[0015] Compared with the prior art, the beneficial effects of the present invention are reflected in: The present invention provides a layered oxide sodium-ion battery cathode material with excellent electrochemical performance, and its chemical formula is Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 . The cathode material prepared by the present invention has long cycle stability and a low cost price, which further promotes the research and development of sodium-ion battery cathode materials.
[0016] At the same time, the cathode material provided by the present invention has an O3-phase structure, which can better maintain the structural stability, promote the transport of sodium ions, and thus obtain more excellent electrochemical performance. In addition, the synthesis method of the cathode material provided by the present invention is simple, has excellent electrochemical performance, and is easy to mass-produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 SEM image of the target product obtained in Example 1.
[0018] Figure 2 XRD spectrum of the target product obtained in Example 1.
[0019] Figure 3 Charge-discharge curve of the target product obtained in Example 1 at a current density of 0.1C.
[0020] Figure 4 Cycle stability spectrum of the target product obtained in Example 1 at a current density of 1C.
[0021] Figure 5 Cycle stability spectrum of the target product obtained in Example 1 at a current density of 5C.
[0022] Figure 6 XRD spectrum of the target product obtained in Example 2.
[0023] Figure 7 Charge-discharge curve of the target product obtained in Example 1 at a current density of 0.1C.
[0024] Figure 8 Charge-discharge curve of the target product obtained in Example 2 at a current density of 1C.
[0025] Figure 9 Cycle stability spectrum of the target product obtained in Example 2 at a current density of 5C.
[0026] Figure 10 XRD pattern of the target product obtained in Example 3.
[0027] Figure 11 Charge-discharge curve of the target product obtained in Example 3 at a current density of 0.1C.
[0028] Figure 12 Charge-discharge curve of the target product obtained in Example 3 at a current density of 1C.
[0029] Figure 13 Cycling stability spectrum of the target product obtained in Example 3 at a current density of 5C. Detailed implementation mode
[0030] The present invention provides a layered oxide sodium-ion battery cathode material co-regulated by multiple metals with excellent cycling stability and rate performance, and the chemical formula is Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 . The sodium-ion battery cathode material provided by the present invention is in a block shape.
[0031] In some specific embodiments of the present invention, the sodium-ion battery cathode material is Na 0.96 Ca 0.02 Ni 0.27 Fe 0. 2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 . Its overall performance is the best, with excellent cycling stability. At a current density of 1C (1C = 150 mA g -1 ), the capacity retention rate is still 91.19% after 200 cycles, which plays a great role in promoting the commercial development of future sodium-ion batteries.
[0032] In the embodiments of the present invention, a sodium-ion battery cathode electrode sheet was successfully prepared, which is prepared from an active material, a conductive additive, a binder, and a solvent, wherein: the cathode active material is the above-mentioned synthesized layered oxide sodium-ion battery cathode material co-regulated by multiple metals; the conductive additive is selected from one or more of carbon black, Super-P, and Ketjenblack; the binder is selected from one or more of polyacrylic acid, sodium carboxymethyl cellulose, polyvinylidene fluoride, and sodium alginate; the solvent is selected from one or more of N-methylpyrrolidone or deionized water.
[0033] In an embodiment of the present invention, a method for preparing the above-mentioned positive electrode sheet of a sodium-ion battery is also provided. The method is to mix a positive electrode material, a conductive additive, and a binder in a certain proportion with a solvent, and then prepare the positive electrode sheet of the battery through subsequent coating and drying processes.
[0034] For the specific methods of the mixing, coating, and drying in the present invention, common preparation methods are adopted, which can be carried out according to the methods well-known to those skilled in the art.
[0035] The present invention also prepares a sodium-ion battery, which is composed of a positive electrode sheet, a separator, an electrolyte, and a negative electrode sodium metal. Among them: the positive electrode sheet adopts the above-mentioned positive electrode sheet of the sodium-ion battery. The electrolyte used is a carbonate-based electrolyte, and the solution concentration is 0.5 - 2 M, preferably 1 M; the solvent in the electrolyte is selected from one or more of dimethyl carbonate, ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, and fluorinated ethylene carbonate, preferably a mixed solvent of propylene carbonate and fluorinated ethylene carbonate; the solute in the electrolyte is selected from one or more of sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, and sodium hexafluorophosphate, preferably sodium perchlorate. The separator is preferably glass fiber.
[0036] The present invention also provides the application of the above-mentioned sodium-ion battery in large-scale energy storage devices such as electric vehicles, solar power generation, wind power generation, smart grid peak shaving, distributed power stations, or communication bases.
[0037] The present invention has the following advantages: (1). The synthesized multi-metal doped bulk layered oxide positive electrode material for sodium-ion batteries, with the chemical formula Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 , has played a great role in promoting the future commercial development of the material system of sodium-ion batteries.
[0038] (2). The positive electrode material Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 has excellent cycle stability and low cost, and is a very promising positive electrode material for sodium-ion batteries.
[0039] (3) The optimal Na in the present invention 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 The cycle stability of the cathode material is the best. After 200 cycles at a current density of 1C (1C = 150 mA g -1 ), its capacity retention rate is 91.19%, which is an ideal cathode material for preparing sodium-ion battery energy storage devices.
[0040] (4) The cathode material synthesized by the method of the present invention has better comprehensive performance compared with the material without multi-metal regulation.
[0041] To further understand the present invention, the excellent performance layered oxide sodium-ion battery cathode material, its preparation method and application provided by the present invention will be described below with specific examples. The protection scope of the present invention is not limited by the following examples. Examples
[0042] Step 1, preparing the Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 cathode material.
[0043] Mix the raw materials such as sodium carbonate, calcium carbonate, nickel oxide, iron(III) oxide, manganese dioxide, aluminum oxide, copper oxide, titanium dioxide, etc. according to the molar ratio and place them in a ball mill tank for ball milling to obtain a mixture powder. Place the mixture powder in a muffle furnace, under an air atmosphere, with a heating rate of 2 o °C / min, heat up to 950 o °C and keep it warm for 15 h. After the heat preservation is completed, cool it down to room temperature to obtain the target product Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 .
[0044] Step 2, preparing the sodium-ion battery cathode sheet.
[0045] Take the synthesized Na 0.96Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 The positive electrode material, Super P, and polyvinylidene fluoride binder (PVDF) are mixed at a mass ratio of 7:2:1, and a certain amount of N-methylpyrrolidone is added as a solvent. After steps such as pulping, coating, and drying in a mixer, a sodium-ion battery positive electrode sheet containing Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 active material is obtained.
[0046] Step 3, assemble a sodium-ion battery using the final product Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 as the positive electrode material.
[0047] Assemble the sodium-ion battery positive electrode sheet prepared above and a sodium metal negative electrode in a glove box. GF / F is used as the battery separator, and a carbonate electrolyte (1M NaClO 4 in PC) is preferably selected as the electrolyte.
[0048] Figure 1 The SEM image of the positive electrode material prepared in Example 1 is shown. It can be seen from the figure that the material has a block structure and is evenly distributed.
[0049] Figure 2 The XRD image of the positive electrode material obtained in Example 1 is shown. It can be seen from the figure that the synthesized layered oxide positive electrode material has an O3-phase structure.
[0050] Figure 3 The charge-discharge curve of the sodium-ion battery assembled with the positive electrode material obtained in Example 1 at a current density of 0.1C (1C = 150 mA g -1 ) is shown. It can be seen from the figure that the synthesized material has a relatively high discharge specific capacity of 130.37 mAh g -1 in the sodium-ion battery.
[0051] Figure 4The figure shows the cycle stability test results of the sodium-ion battery assembled with the positive electrode material obtained in Example 1 at a current density of 1C. As can be seen from the figure, after 200 cycles, the capacity retention rate is still 91.19%.
[0052] Figure 5 The figure shows the cycle stability test results of the sodium-ion battery assembled with the positive electrode material obtained in Example 1 at a current density of 5C. As can be seen from the figure, after 1000 cycles, the capacity retention rate is still 76.58%. Example
[0053] The preparation method is the same as that of Example 1, except that the raw material ratio is added according to the stoichiometric ratio of NaNi 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 .
[0054] Figure 6 The figure shows the XRD pattern of the NaNi 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 material obtained in Example 2. As can be seen from the figure, the synthesized positive electrode material has good crystallinity and is also in the O3 phase structure.
[0055] Figure 7 The figure shows the charge-discharge curve of the sodium-ion battery assembled with the NaNi 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O 2 positive electrode material at a current density of 0.1C (1C = 150 mA g -1 ). As can be seen from the figure, the synthesized material has a discharge specific capacity of 128.7 mAh g -1 in the sodium-ion battery.
[0056] Figure 8 The figure shows the cycle stability test results of the sodium-ion battery assembled with the positive electrode material obtained in Example 1 at a current density of 1C. As can be seen from the figure, after 200 cycles, the capacity retention rate is 86.21%.
[0057] Figure 9The figure shows the cyclic stability test results of the sodium-ion battery assembled with the cathode material obtained in Example 1 at a current density of 5C. It can be seen from the figure that after 1000 cycles, the capacity retention rate is still 64.9%. Example
[0058] The preparation method is the same as that of Example 1, except that the raw material ratio is added according to the stoichiometric ratio of NaNi 0.4 Fe 0.2 Mn 0.4 O 2
[0059] Figure 10 The figure shows the XRD pattern of the NaNi 0.4 Fe 0.2 Mn 0.4 O 2 material obtained in Example 3. It can be seen from the figure that the synthesized cathode material has good crystallinity and is of the O3 phase structure.
[0060] Figure 11 The figure shows the charge-discharge curve of the sodium-ion battery assembled with the NaNi 0.4 Fe 0.2 Mn 0.4 O 2 cathode material obtained in Example 3 at a current density of 0.1C (1C = 150 mA g -1 ) current density. It can be seen from the figure that the synthesized material has a discharge specific capacity of 135.89 mAh g -1 in the sodium-ion battery.
[0061] Figure 12 The figure shows the cyclic stability test results of the sodium-ion battery assembled with the cathode material obtained in Example 1 at a current density of 1C. It can be seen from the figure that after 200 cycles, the capacity retention rate is 60.28%.
[0062] Figure 13 The figure shows the cyclic stability test results of the sodium-ion battery assembled with the cathode material obtained in Example 1 at a current density of 5C. It can be seen from the figure that after 1000 cycles, the capacity retention rate is still 26.75%.
[0063] Although the embodiments of the present invention have been disclosed as above, it is not limited to the applications listed in the specification and embodiments. It can be fully applied to various fields suitable for the present invention. For those skilled in the art, additional modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to specific details.
Claims
1. A multi-metal co-regulated layered oxide sodium ion battery positive electrode material, characterized in that: The chemical formula of the sodium ion battery positive electrode material is Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O2.
2. A method for preparing a multi-metal co-regulated layered oxide sodium ion battery positive electrode material as claimed in claim 1, characterized in that: The sodium ion battery positive electrode material is prepared and synthesized by a solid phase method.
3. The preparation method according to claim 2, characterized in that: The steps of preparing multi-metal co-regulated layered oxide sodium ion battery positive electrode materials by solid phase method are as follows: Putting a sodium source compound, a nickel source compound, a copper source compound, a calcium source compound, an iron source compound, a manganese source compound, an aluminum source compound, and a titanium source compound in a mortar according to a molar ratio, and grinding them until they are fully mixed to obtain a precursor powder sample; The precursor powder sample is calcined to finally obtain a multi-metal co-regulated layered oxide sodium ion battery positive electrode material Na 0.96 Ca 0.02 Ni 0.27 Fe 0.2 Mn 0.35 Al 0.02 Cu 0.1 Ti 0.05 O2.
4. The preparation method according to claim 3, characterized in that: The sodium source compound is one or more of sodium oxalate, sodium nitrate, sodium chloride, sodium acetate and sodium citrate; the nickel source compound is one or more of nickel oxalate, nickel nitrate, nickel chloride, nickel acetate and nickel sulfate.
5. The preparation method according to claim 3, characterized in that: The copper source compound is one or more of copper oxalate, copper nitrate, copper chloride, copper acetate and copper sulfate; the calcium source compound is one or more of calcium oxide, calcium bicarbonate, calcium chloride, calcium bromide and calcium iodide.
6. The preparation method according to claim 3, characterized in that: The iron source compound is ferric oxalate, ferric nitrate, ferric chloride, ferric acetate and ferric sulfate; the manganese source compound is one or more of manganese oxalate, manganese nitrate, manganese chloride, manganese acetate and manganese sulfate.
7. The preparation method according to claim 3, characterized in that: The aluminum source compound is one or more of aluminum oxide, aluminum hydroxide, aluminum nitrate, aluminum phosphate and aluminum sulfate; the titanium source compound is one or more of titanium dioxide, titanium tetrachloride, sodium titanate and titanium phosphate.
8. The preparation method according to claim 3, characterized in that: The calcination is carried out in an air atmosphere, the temperature is raised to 950° C., the heating rate is 2° C. / min, the heat preservation time is 15 hours, and the final sample is obtained after cooling to room temperature.
9. A sodium ion battery positive electrode sheet, prepared from a positive electrode material, a conductive additive, a binder and a solvent, characterized in that: The positive electrode material is selected from the multi-metal co-regulated layered oxide sodium ion battery positive electrode material described in claim 1.
10. A sodium ion battery, comprising a positive electrode sheet, a separator, an organic electrolyte and a negative electrode metallic sodium, characterized in that: The positive electrode sheet is the positive electrode sheet for a sodium ion battery according to claim 9.
Citation Information
Patent Citations
High-entropy doped layered oxide, preparation method thereof, positive electrode material and sodium ion battery
CN116425212A
High-entropy doped O3 phase layered oxide and preparation method thereof, sodium ion battery positive electrode material and battery
CN116605918A
Al, Zn, Ti and Fe co-doped biphase layered oxide sodium ion battery high-entropy positive electrode material
CN116805684A
Double-site metal ion doped nickel iron sodium manganate positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery
CN118315567A
Layered sodium ion high-entropy oxide positive electrode material and preparation method and application thereof
CN118431441A